Оптимізація зйомки відео для подальшого виконання морфінгу - Сидоров, Є. О. (ХНУРЕ, 2025)
This work focuses on optimizing video shooting techniques for seamless morphing. It highlights key factors such as camera stability, lighting uniformity, accurate focusing, and proper object positioning to ensure smooth transitions and minimize visual artifacts. The research emphasizes the importance of controlled motion, consistent framing, and appropriate equipment usage, such as tripods and stabilizers. Recommendations are provided to enhance video quality and facilitate post-processing, ensuring accurate morphing results. Proper organization of the shooting process significantly reduces distortions and simplifies subsequent editing, leading to more natural and visually appealing transformations.
Keywords: зйомка відео; виконання морфінгу